Review of Criminal Law Sanctions on Damaged Coral Reefs - Afifa Fadillah, Siti (Lex Scientia Law Review, 2019)
The problem that is currently unresolved is the destruction of marine ecosystems, namely coral reefs. Coral reefs have many important roles in marine ecosystems. Coral reefs have 100 years to reach a height of 1 meter. There are 2 causes of the destruction of coral reefs, namely: natural and human factors. Natural factors are also caused by humans (again) namely global warming. It is this human action that really likes to exploit this underwater beauty, making it almost disappear and partially damaged. The action of the 'hunter' did not feel the impact. However, they will feel our grandchildren later. This is really a serious problem and any human behavior that damages coral reefs, either directly or indirectly, deserves to be categorized as an extraordinary crime as stipulated in Law No. 27 of 2007. The sanctions they receive are in the form of large fines and imprisonment for a long time.